2007
DOI: 10.1007/s10457-007-9036-y
|View full text |Cite
|
Sign up to set email alerts
|

Driving competitive and facilitative interactions in oak dehesas through management practices

Abstract: Dehesas are extant multi-purpose agroforestry systems that consist of a mosaic of widely-spaced scattered oaks (Quercus ilex L.) combined with crops, pasture or shrubs. We aimed to clarify the role of trees in dehesas of CW Spain focussed on the analysis of treeunderstorey interactions. Spatial variability of resources (light, soil moisture and fertility), microclimate, fine roots of both herbaceous plants and trees and forage yield was measured. Additionally, we compared the nutritional and physiological stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(30 citation statements)
references
References 28 publications
5
14
0
Order By: Relevance
“…In the present study, < wpd values showed a small variation during the drought season, following the pattern reported by Cubera and Moreno (2007) and Moreno et al (2007) for Quercus ilex trees growing in a drier site (precipitation: 500-600 mm), with deeper soils and lower tree density (9-35 trees/ha). However, our results are not in total agreement with those reported by David et al (2007) for both Q. ilex and Q. suber stands (about 30 trees/ha) under Mediterranean conditions in southern Portugal (665 mm, 15Cº), in which much lower values (-1.7 to -2.3 MPa) were observed in summer.…”
Section: Discussionsupporting
confidence: 74%
“…In the present study, < wpd values showed a small variation during the drought season, following the pattern reported by Cubera and Moreno (2007) and Moreno et al (2007) for Quercus ilex trees growing in a drier site (precipitation: 500-600 mm), with deeper soils and lower tree density (9-35 trees/ha). However, our results are not in total agreement with those reported by David et al (2007) for both Q. ilex and Q. suber stands (about 30 trees/ha) under Mediterranean conditions in southern Portugal (665 mm, 15Cº), in which much lower values (-1.7 to -2.3 MPa) were observed in summer.…”
Section: Discussionsupporting
confidence: 74%
“…The role of trees as biogeochemical processes regulators in montado soils has been widely acknowledged, being commonly associated with the effect of tree litterfall deposition (Moreno et al, 2007;Gallardo et al, 2000). Results of the present study regarding net N mineralization rate and microbial biomass C and N are in agreement with this balancing effect, as under tree crown they were independent on pasture management type.…”
Section: And N Dynamicssupporting
confidence: 79%
“…In this case the reduced soil depth affected the recovery of the cork oak system because it was located mainly in flat or gentle slopes where the anthropogenic disturbances are higher. The compacted parent material with significant clay content (Inverno et al 1993) may also reduce the tree deep-rooting pattern (Fisher and Binkley, 2000) that could result in a higher dependence on the water and nutrients in the uppermost soil horizons in direct competition with the better-adapted understory (Barbero et al 1990;Moreno et al 2007). In Luvisols, the anthropogenic disturbances like grazing and livestock had a strong negative effect on cork oak recovery and the balance between expansion and regression of cork oak forest was negative.…”
Section: Cork Oak Landscape Dynamicsmentioning
confidence: 97%